A silk fibroin hydrogel with reversible sol–gel transition. Issue 39 (5th May 2017) - Yin, Zhuping; Wu, Feng; Xing, Tieling; Yadavalli, Vamsi K.; Kundu, Subhas C.; Lu, Shenzhou
Abstract : Herein, we prepare a novel silk fibroin hydrogel with a reversible thixotropic gel–sol transition triggered by a facile cycled shearing and resting procedure. Abstract : In this report, a novel silk fibroin hydrogel with a reversible sol–gel transition capacity is presented, in which the base material of this reversible hydrogel is hydrophilic silk fibroin (HSF) obtained by immersing a dried regenerated Bombyx mori silk fibroin (SF) condensate in deionized water (DI water) and collecting its lixivium. The resulting HSF sol can exhibit an enhanced sol–gel transition within several hours at suitable temperatures (25–50 °C) without any exterior additive, even at extremely low concentrations (<0.2%, w/v). The HSF gel can perform thixotropic, reversible gel–sol transitions triggered by a facile cycled shear-thinning and resting procedure. Reversible sol–gel transition kinetics analyses and dynamic measurements of the micro-structure transformation during the transition demonstrate that both the β-sheet self-assembling process and metastable hydrogen bonding (H-bond) interactions among these large scale β-sheet aggregates play essential roles in the significant enhancement of the reversible HSF sol–gel transition. Due to the reversible, thixotropic sol–gel transitions and suitable viscoelasticity of its shear-thinning system for matching random sizes/shapes, the HSF system is possibly an alternative injectable hydrogel for applications in 3-dimensional (3D) cell culture and tissue repair in situ .